2018
DOI: 10.1161/circulationaha.117.032561
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women With Rheumatic Mitral Valve Disease

Abstract: Although mortality was only 1.9% during pregnancy, ≈50% of the patients with severe rheumatic MS and 23% of those with significant MR developed heart failure during pregnancy. Prepregnancy counseling and considering mitral valve interventions in selected patients are important to prevent these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 31 publications
4
58
1
5
Order By: Relevance
“…The predominance of complicated RHD seen among pregnant women in our study mirrors the disproportionate burden of RHD disease seen among women of reproductive age in SSA, where RHD remains endemic [5,22,29]. Data from the Registry of Pregnancy and Cardiac Disease (ROPAC), the largest registry of pregnant women with cardiac disease globally, illustrates that 55% of women enrolled from LMICs had valvular heart disease, predominantly rheumatic mitral stenosis, and studies from South Africa estimate that RHD accounts 71-84% of all cases of antenatal heart disease [16,18,21,23]. Additionally, more than half of our cases had severe mitral stenosis and/or pulmonary hypertension, both of which can be contraindications to pregnancy [8,11,17].…”
Section: Discussionsupporting
confidence: 60%
“…The predominance of complicated RHD seen among pregnant women in our study mirrors the disproportionate burden of RHD disease seen among women of reproductive age in SSA, where RHD remains endemic [5,22,29]. Data from the Registry of Pregnancy and Cardiac Disease (ROPAC), the largest registry of pregnant women with cardiac disease globally, illustrates that 55% of women enrolled from LMICs had valvular heart disease, predominantly rheumatic mitral stenosis, and studies from South Africa estimate that RHD accounts 71-84% of all cases of antenatal heart disease [16,18,21,23]. Additionally, more than half of our cases had severe mitral stenosis and/or pulmonary hypertension, both of which can be contraindications to pregnancy [8,11,17].…”
Section: Discussionsupporting
confidence: 60%
“…Study designs affected the quality and were subject to high levels of bias, especially the case series. Referral and other selection biases as acknowledged in several papers were particularly related to the predominantly single‐site tertiary‐care‐level settings.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐six studies specified echocardiographic review during pregnancy, although only four referenced diagnostic criteria . Six studies did not specify RHD diagnosis confirmed by echocardiography, nor its use during pregnancy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations